Teachers’ reflections on the practicality of English in-service courses in Iran - Baniasad-Azad, Somayeh; Tavakoli, Mansoor; Ketabi, Saeed (Penerbit Universiti Kebangsaan Malaysia, 2017)
As professional development is essential for teacher quality, many countries have made investments in designing teacher education programs. The study explores the efficacy of in-service courses in Iran from the perspective of English language teachers. Interviews were conducted to examine teachers’ beliefs about the efficacy of in-service courses, their involvement in program development, the application of program material by teachers, and their preferences about teacher education programs. The findings showed that program designers adopted a traditional transmissive model to transfer pre-determined knowledge to the teachers without involving teachers in the decision making process. Teachers, in turn, did not apply the program materials in their teaching practices because they believed program materials were idealistic, impractical, generalized, and decontextualized. Moreover, what teachers considered beneficial for their development was different from what was presented to them in the in-service courses. The reason for such inconsistencies is a lack of communication and effective feedback channel between teachers and planners. The findings suggest that as teachers are the final decision makers based on the realities of their teaching situation, involving them in planning and program development process can decrease the existing gap and make program materials more realistic and consequently applicable. Implications for language planning and teacher education programs are discussed.